2002
DOI: 10.1111/j.1748-0361.2002.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Policies Responsive to Barriers to Health Care Among Rural Residents: WhatDo We Need to Know?

Abstract: A substantial body of research has been devoted to the subject of access to health care services for rural residents, much with the intention of shaping government policies to remove barriers or equalize the distribution of health care services. A number of programs and policies have grown out of or been affected by access research, yet despite identifiable successes of the policy research process, barriers to health care services still exist in rural areas. This article attempts to stimulate discussion about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Research in Australia also suggests that patients from rural areas are more at risk of an ACS admission than those not in a rural area, implying access to primary care is an issue [7,18]. Slifkin reports that health care seeking behaviour may also differ between rural and urban residents [19]. Kirby et al identified that the location of services, lack of transport to services and waiting times for services were barriers to accessing primary health care in rural areas [2].…”
Section: Discussionmentioning
confidence: 99%
“…Research in Australia also suggests that patients from rural areas are more at risk of an ACS admission than those not in a rural area, implying access to primary care is an issue [7,18]. Slifkin reports that health care seeking behaviour may also differ between rural and urban residents [19]. Kirby et al identified that the location of services, lack of transport to services and waiting times for services were barriers to accessing primary health care in rural areas [2].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be salient primarily in rural areas where travel distances are greater, pharmacies are fewer, and public transportation is scarce. 20 …”
Section: Discussionmentioning
confidence: 99%
“…18,19 For people living in rural areas, deciding whether to fill a prescription may entail the additional considerations of travel inconvenience and transportation challenges posed by greater distances to pharmacies, as to all services, in rural areas. 20 Rates of primary medication non-adherence and its causes have not been studied in rural populations, to our knowledge.…”
mentioning
confidence: 99%
“…As an explanation, they suggest that "social values and norms associated with rural life may discourage the use of preventive services" (p. 208). The reason is that rural residents may "link the need for health care services with an inability to carry out normal role functions" (Slifkin, 2002). The idea is that, relative to urban residents, rural residents may be less likely to seek out medical care if they believe their ability to perform their roles is not significantly impaired, but they obtain medical care when problems are considered to be severe.…”
Section: Beliefs and Values Of Rural Versus Urban Areasmentioning
confidence: 99%